2023
DOI: 10.21203/rs.3.rs-2594802/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A proteomic study indicating susceptibility to excitotoxicity induced by the N-methyl-D- aspartate receptor hyperfunction as a potential mechanism underlying differences in cognitive function between males and females in a Thai healthy population

Abstract: Intact cognitive function is dependent on the precise exchange of information between neurons. Sex differences in cognitive function exist, but they are not stable, undergoing dynamic change during the lifespan. However, our understanding of how sex-related neural information transmission evolves with age is still in its infancy. This study was designed to investigate the molecular mechanisms underlying age-related sex differences in cognitive function in a Thai healthy population, as well as to determine the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…In contrast, females did worse in the primary education group for both %Corrects and %Errors, with fewer correct responses and more errors. The total errors of WCST reflect non-specific cognitive impairments, and another research we conducted suggested that females might be more susceptible to the excitotoxicity induced by WCST [59]. This, combined with the loss of estrogen's neuroprotection effects after menopause [60][61][62], led to loss of brain environment homeostasis and impaired cognitive function in elderly female subjects [59].…”
Section: Plos Onementioning
confidence: 90%
“…In contrast, females did worse in the primary education group for both %Corrects and %Errors, with fewer correct responses and more errors. The total errors of WCST reflect non-specific cognitive impairments, and another research we conducted suggested that females might be more susceptible to the excitotoxicity induced by WCST [59]. This, combined with the loss of estrogen's neuroprotection effects after menopause [60][61][62], led to loss of brain environment homeostasis and impaired cognitive function in elderly female subjects [59].…”
Section: Plos Onementioning
confidence: 90%